The role of digital tools and e-learning platforms in enhancing Arabic learning for non-native speakers - Nasirudeen, Abdulwasiu; Chtaibi, Khalid (Al-Madinah International University (MEDIU) Malaysia, 2025)
The rise of digital tools and e-learning platforms has significantly transformed language learning, offering new opportunities for learners worldwide, including non-native speakers of Arabic. This paper explores the role of these digital resources in enhancing the acquisition of Arabic, a language known for its complex script, diverse dialects, and unique linguistic features. By examining the strengths and limitations of various digital platforms—such as language learning apps, online courses, and interactive software— this study investigates how these tools address the challenges faced by learners. Specifically, it focuses on aspects such as accessibility, interactivity, personalized learning, and cultural immersion, evaluating how well digital tools support the development of reading, writing, listening, and speaking skills in Arabic. Through a combination of literature review, case studies, and learner feedback, the paper highlights the effectiveness of e-learning platforms in facilitating Arabic language acquisition, while also addressing the gaps that still exist, particularly in area such as pronunciation and dialectical variations. The findings suggest that, while digital tools offer valuable support, a blended approach combining both digital and traditional methods may be the most effective strategy for promoting long-term language mastery. This research contributes to the growing field of digital language education by offering insights into the pedagogical implications of e-learning in Arabic and providing recommendations for future developments in this area.